Revisiting the Age-Prospective Memory Paradox Using Laboratory and Ecological Tasks - Koo, Yu Wen; Neumann, David L.; Ownsworth, Tamara; Shum, David H. K. (Frontiers in Psychology, 2021)
Prospective memory (PM) is the ability to perform a planned action at a future time. Older adults 14 have shown moderate declines in PM which are thought to be driven by age-related changes in 15 the prefrontal cortex. However, an age-PM paradox is often reported, whereby deficits are 16 evident in laboratory-based PM tasks, but not naturalistic PM tasks. The key aims of this study 17 was to: 1) examine the age-PM paradox using the same sample across laboratory and ecological 18 settings; and 2) determine whether self-reported PM and cognitive factors such as working 19 memory and IQ are associated PM performance. Two PM tasks were administered (ecological 20 vs. laboratory) to a sample of 23 community-dwelling older adults (Mage = 72.30, SDage = 5.62) 21 and 28 young adults (Mage = 20.18, SDage = 3.30). Participants also completed measures of 22 general cognitive function, working memory, IQ, and self-reported memory. Our results did not 23 support the existence of the age-PM paradox. Strong age effects across both laboratory and 24 ecological PM tasks were observed in which older adults consistently performed worse on the 25 PM tasks than young adults. In addition, PM performance was significantly associated with self-26 reported PM measures in young adults. For older adults, IQ was associated with time-based PM. 27 These findings suggest that the age-PM paradox is more complex than first thought and there are 28 differential predictors of PM performance for younger and older adults.